Beyond the Domestic Sphere: Navigating Shifting Gender Roles through the Lens of Islamic Jurisprudence - Lukhi Nur Azizah; Shinta Octarina (Al-Fiqh: Journal of Contemporary Islamic Law, 2025)
This study aims to evaluate the shifting domestic roles of women in Muslim families and the corresponding adaptive responses within Islamic jurisprudence. The background is marked by global socio-economic transformations that have propelled women into significant professional roles, creating tensions with traditional patriarchal interpretations of family law. Employing a qualitative-descriptive approach via library research, this study synthesizes classical and contemporary Islamic texts. The methodology integrates normative-juridical and socio-legal frameworks to bridge the gap between sacred texts and social change. Findings demonstrate a fundamental transition toward a collaborative family model in which authority is an achieved status based on contribution rather than on ascribed gender. Jurisprudentially, this shift is facilitated by reinterpreting Qiwamah as a functional, maintenance-based responsibility. Furthermore, Maqasid al-Shari’ah and Ijtihad provide robust teleological justifications for women’s dual roles. However, a significant "legal gap" persists due to literalist hermeneutics and patriarchal norms. The study concludes that a gender-aware hermeneutic is essential to harmonize Sharia with modern justice. This research contributes a constructive synthesis for contextualizing Islamic family law and recommends a principle-oriented approach to ensure legal relevance in the 21st century.